TLM analysis of metal contacts for 2D MoS2 nanoflakes deposited by chemical vapour deposition-free technique - Zakaria, Rozalina; Tan, Chee Long (Malaysian NANO-An International Journal, 2022)
In the past decade, two-dimensional (2D) nanomaterials are gaining significant attention due to their novel properties in electrical, optical, mechanical which are different from their bulk forms. Therefore, it becomes one of the most promising materials for sensing applications. However, to connect the 3D world with 2D materials require excellent communication links which is a contact that renders remarkable electrical properties and specifically 2D nanomaterials-based sensor has been suffering from high resistance and low sensitivity due to the loss caused by poor contact between the 2D nanomaterials and metal interface. This work explores the electrical properties of metal/2D contacts by the rectangular transmission line method (TLM). The critical resistance parameters such as sheet and specific contact resistance were determined by characterizing the current-voltage (IV) relation. The behavior of different metals (silver and gold) contacts to 2D MoS2 nanoflakes deposited on Si substrate by low-cost spray coating technique are observed. These metals are chosen based on the work function relative to the electron’s affinity, χ of MoS2. UV-Vis’s analysis is carried out to estimate the final concentration of MoS2 solution.